Is tapentadol a potential Trojan horse in the postdextropropoxyphene era in India? - Basu, Aniruddha (Indian J Pharmacol, 2018)
Tapentadol is a centrally acting opioid analgesic which has partial opioid agonistic and norepinephrine reuptake inhibitor action similar to its nearest congener and tramadol though with a relatively higher μ-affinity. It has abuse potential, is a scheduled drug, yet currently is not known to be an opioid widely misused in India. However, under the current drug abuse legislation in India, where common prescription opioids such as dextropropoxyphene have been banned, tapentadol may take the center stage of pharmaceutical opioid abuse in the near future. We present a series of two cases where the opioid use started with codeine, dextropropoxyphene, and buprenorphine but moved on to tapentadol and tramadol due to ease of access and cost. These cases highlight the potential of tapentadol in replacing dextropropoxyphene as the widespread prescription opioid of abuse and also emphasize the current controversies regarding opioid control policies in India.